2019
DOI: 10.1002/joc.6347
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts under representative concentration pathway scenarios on streamflow and droughts of basins in the Brazilian Cerrado biome

Abstract: Brazilian Cerrado biome is the largest and richest tropical savanna in the world. In order to understand the effects of climate changes on the hydrology of the Cerrado basins, this paper investigates the hydrological impacts of climate change throughout the 21st century under different emissions scenarios on the streamflow and on the droughts in the Sono, Manuel Alves da Natividade and Palma basins, located in the Brazilian Cerrado. For this purpose, the SWAT hydrological model driven by the downscaling of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 47 publications
3
29
0
3
Order By: Relevance
“…Studies suggest an increase in the intensity and frequency of droughts by the end of the century worldwide due to atmospheric evaporative demand increases, reducing water availability, soil water storage, and agricultural production [15,33,34]. Yet, Santos et al [35] observed a reduction in the water table in the PRB wetlands, downstream of the streamflow gauge station of this study, due to a The most significant meteorological droughts occurred during the hydrological years of 1986/87, 1994/95, 1995/96, 1997/98, 2007/08, and between 2014/15 and 2016/17 in the PRB.…”
Section: Meteorological and Hydrological Droughtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest an increase in the intensity and frequency of droughts by the end of the century worldwide due to atmospheric evaporative demand increases, reducing water availability, soil water storage, and agricultural production [15,33,34]. Yet, Santos et al [35] observed a reduction in the water table in the PRB wetlands, downstream of the streamflow gauge station of this study, due to a The most significant meteorological droughts occurred during the hydrological years of 1986/87, 1994/95, 1995/96, 1997/98, 2007/08, and between 2014/15 and 2016/17 in the PRB.…”
Section: Meteorological and Hydrological Droughtsmentioning
confidence: 99%
“…During the period 2013/14 to 2017/18, similar events were found in other Brazilian regions such as the Doce river basin [14], Tocantins river basin [12], Northeastern Brazil [36], Amazon [36], Paraná river basin [37], the metropolitan region of São Paulo [38], and Ceará State [9], affecting the hydropower generation and urban supply. Besides, droughts can affect the ecological functions of the Brazilian savanna [34], as well as reduce the native fish species and increase exotic species [39].…”
Section: Meteorological and Hydrological Droughtsmentioning
confidence: 99%
“…However, simulations from RCMs, such as Eta, are subjected to systematic biases (Graham et al, 2007;Rodrigues et al, 2020), mainly caused by errors in conceptualization, discretization and spatial average of climate variables within a grid-cell (Teutschbein and Seibert, 2012).…”
Section: Climate Models Downscaling and Bias Correctionmentioning
confidence: 99%
“…The period from January 2002 to December 2010 was used for calibration. The initial ranges of the parameters used in calibration were selected based on previous studies conducted in the Cerrado biome, such as Oliveira et al [27] and Rodrigues et al [61]. Subsequently, the parameters were adjusted for the study area through two iterations with 500 simulations each through the SUFI-2 algorithm implemented in SWAT-CUP.…”
Section: Calibration and Validation Of The Swat Modelmentioning
confidence: 99%
“…The average KGE values of IMERG were slightly better than TMPA. Table 2 presents the parameters that were used in the SWAT model with their respective initial ranges, which were selected from the literature review of hydrological modeling studies in the Brazilian Cerrado biome [27,61], and the range of the parameters obtained by SUFI2. It is interesting to highlight that the simulations driven by IMERG and rain gauges resulted in similar parameter values.…”
Section: Meteorological and Hydrological Evaluationmentioning
confidence: 99%